(untitled) (International Seven Journal of Health Research, 2024)
Congenital cataracts, characterized by opacity of the lens present at birth or that develop in childhood, require a meticulous diagnostic approach to differentiate it from other ocular pathologies that have similar symptoms. One of these conditions is the persistence of the primary pupillary membrane, in which embryological remnants can simulate opacities in the lens, confounding the initial diagnosis. Another important condition to consider is retinoblastoma, a malignant tumor of the retina that can manifest with leukocoria, a clinical sign often confused with congenital cataracts. Exclusion of this tumor is essential due to the potential severity and differential treatment it requires. In addition, lens coloboma, a congenital malformation that results in a cleft or partial absence of the lens, should be carefully evaluated as it can be mistaken for cataracts, but requires a distinct therapeutic approach. Accurate diagnosis of these conditions is not only vital for determining the appropriate treatment, but also for preventing serious visual complications and planning early interventions that can significantly improve long-term visual outcomes. Differentiation between these pathologies is therefore an essential component in the effective management of congenital cataracts.